BNDES and the internationalization of Brazilian companies on Lula governments: Embraer's case - Maia, Eduardo Santos; Alves, Davi Soares (Faculdade de Filosofia e Ciências, 2021)
This paper aims to analyze the dynamics of the internationalization of nationally-based companies in Lula governments. We argue that the main tool in this process was the Banco Nacional de Desenvolvimento Econômico e Social (BNDES), with emphasis on companies capable of competing internationally. The new foreign policy is also emphasized as the political-ideological basis that made such procedures possible. We explore Embraer's case for it illustrates the synthesis of political and economic interests of the period and how those interests were pursued by the governments. The analysis was based on BNDES' official documents and on specialized literature. We made an effort to incorporate different perspectives to create a more complete analytical framework. The BNDES-Embraer relationship was positive not only for the company but as a strategic part in achieving the new foreign policy guidelines. BNDES's support to Embraer was instrumental, particularly in times of crisis, and helped to maintain its competitiveness at the international level with positive effects on the economy.